The Influence of the Implementation of Information Technology and Organizational Culture on Employee Work Motivation Through Leadership Style at PT PLN (Persero) North Sumatra UID - Boy Rocky S; Elfitra Desi; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study focuses on examining how information technology implementation and organizational culture affect employee work motivation, with an emphasis on leadership style at PT PLN (Persero) UID North Sumatra. A quantitative approach was adopted for this study, where data were collected through questionnaires. This study involved a sample of 100 employees, selected through a census method. Data analysis used Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that information technology implementation and organizational culture had a positive and significant effect on leadership style. Furthermore, organizational culture and leadership style also had a positive and significant effect on employee work motivation. On the other hand, information technology implementation did not have a direct effect on work motivation. However, leadership style was found to act as a mediator between the impact of information technology implementation and organizational culture on employee work motivation. Therefore, it can be concluded that leadership style is very important in improving employee work motivation by utilizing information technology and cultivating a positive organizational culture.